Comparative study of the phenolic profile and antioxidant properties of Chamaemelum nobile: infusion, decoction, and hydroalcoholic extract - Guimarães, Rafaela (2012)
This stud} aimed to determine the phenolic composition and to evaluate the antioxidant activity o f different preparation' of Roman chamomile: infusion. decoction and methanol: water (80:20) extract. The hydroalcoholic extract revealed the highest antioxidant activity in almost all the performed assays (EC\ , ≤0.62 mg/ml. depending on the assay ). which was in agreement with its highest total content in phenolic compounds. Otherwise. decoctions presented the lowest antioxidant potential (EC50 ≤1.4S mg/mL. depending on the assay). The phenolic profile of the different preparations was identical. varying only in the concentrations found. Phenolic acids (caffooylquinic acids). flavonols (quercetin and kaempferol derivatives) and flavones (apigenin and luteolin derivatives) were found in the three preparations. The most abundant compounds in the infusion and hydroalcoholic ex tract we re 5-0 -caffeoylquinic acid and an apigenin derivative. These. as also the other phenolic compounds, decreased significantly in the decoction .